The butterflies of the northern Aegean Island of Gökçeada (Imros) (Lepidoptera: Papilionoidea & Hesperioidea) - S. Seven (SHILAP Revista de lepidopterología, 2008)
In this study, butterflies collected from Gökçeada are presented, including old records from the literature. Seven species collected during the course of this study [Allancastria cerisyi (L., 1758), Leptidea sinapis (L., 1758), Issoria lathonia (L., 1758), Plebicula thersites (Cantener, [1835]), Pseudophilotes vicrama (Moore, 1865), Tarucus balkanicus (Freyer, [1844]), Glaucopsyche alexis (Poda, 1761)] are the first record for the Gökçeada. With this study the number of species from Gökçeada was raised from 45 to 52. Seven species are proposed for endangered (E) status and 13 species for vulnerable (VU) status.